2017
DOI: 10.3177/jnsv.63.208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Obesity Effect between Two Types of Syrup Containing Rare Sugars in Wistar Rats

Abstract: Summary d-Allulose-containing rare sugar sweeteners have been categorized into two types, rare sugar syrup (RSS), consisting of 4 rare monosaccharides, and modified glucose syrup (MGS), rich in d-allulose, which was previously referred to d-psicose. The anti-obesity effect of RSS and d-allulose has been already clarified, but that of rare monosaccharides other than d-allulose in RSS has not yet been well understood. Here, we investigated and compared the anti-obesity effect of RSS and MGS in rats. Male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…A further 6 studies induced obesity and hyperglycaemia in wildtype animals by feeding high-sucrose or high-fat diets. Of these, three found no significant differences in blood glucose or insulin with PSI (61; 62) or RSS (63) feeding. Reductions in fasting blood glucose were reported in two studies feeding PSI to mice with diet-induced obesity (DIO) (41; 42) , and Pongkan et al (64) , found significant reductions in fasting insulin levels and insulin resistance when PSI was fed to obese Wistar rats.…”
Section: Rare Sugars and Glycaemic Controlmentioning
confidence: 87%
See 4 more Smart Citations
“…A further 6 studies induced obesity and hyperglycaemia in wildtype animals by feeding high-sucrose or high-fat diets. Of these, three found no significant differences in blood glucose or insulin with PSI (61; 62) or RSS (63) feeding. Reductions in fasting blood glucose were reported in two studies feeding PSI to mice with diet-induced obesity (DIO) (41; 42) , and Pongkan et al (64) , found significant reductions in fasting insulin levels and insulin resistance when PSI was fed to obese Wistar rats.…”
Section: Rare Sugars and Glycaemic Controlmentioning
confidence: 87%
“…Han 2020 (44) + Choi 2018 (71) *+ Hossain 2011 (43) Itoh 2015 (46) Kim 2017 (73) + Ochiai 2013 (62) Ochiai 2017 (63) +* PSI Chen (48) *+# Chen (49) *+ Improved plasma lipid profile TAG Ensor 2015 (40) PSI TAG Han 2016 (42) +, 2020 (44) +, 2020 (45) + Baek 2010 (58) Choi 2018 (71) *+ Do 2019 (41) + Ochiai 2013 (62) Hossain 2015 (60) Kim 2017 (73) + Kanasaki 2019 (61) *+ Williams 2015 (91) *+ PSI Chen (48) *+# Chen (49) *+ Reduced hepatic lipid accumulation PSI Han 2016 (42) +, 2020 (44) +, 2020 (45) + Do 2019 (41) + Hossain 2011 (43) PSI Chen (49) *+ ALL Itoh 2015 (46) Yamamoto 2017 (27) Improved gut microbiome PSI TAG Han 2020 (44) +, 2020 (45) + Son 2019 (47) Reduced inflammation PSI TAG…”
Section: Rssmentioning
confidence: 99%
See 3 more Smart Citations